Testing optimum viewing conditions for mammographic image displays...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Waynant RW; Chakrabarti K; Kaczmarek RA; Dagenais I (Journal of Digital Imaging)
The viewbox luminance and viewing room light level are important parameters in a medical film display, but these parameters have not had much attention. Spatial variations and too much room illumination can mask real signal or create the false perception of a signal. This presentation looks at how scotopic light sources and dark-adapted radiologists may identify more real diseases. Copyright (c) 1999 by W.B. Saunders Company